Preparation method of iron-doped zinc oxide semiconductor film with adjustable and controllable light-emitting wavelength, iron-doped zinc oxide semiconductor film and application of iron-doped zinc oxide semiconductor film

By adopting specific steps in the preparation of iron-doped zinc oxide films, including dissolution, heating and stirring, film making and heat treatment, the problem of difficult doping concentration is solved, and the stability of film performance and reduction of production costs are achieved.

CN119725081APending Publication Date: 2025-03-28YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411808191.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the process of preparing iron-doped zinc oxide semiconductor thin films, the doping concentration is difficult to control, resulting in unstable film performance and high production costs.

Method used

A method including steps is adopted: first dissolve zinc acetate and iron acetylacetonate in ethylene glycol methyl ether, then add ethanolamine solution and heat stirring, then use a homogenized film and heat treatment in a sintering furnace to prepare an iron-doped zinc oxide film.

Benefits of technology

This method can stabilize the doping concentration of the iron-doped zinc oxide film, reduce production costs, and achieve efficient film preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725081A_ABST
    Figure CN119725081A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an iron-doped zinc oxide semiconductor film with adjustable and controllable light-emitting wavelength, the iron-doped zinc oxide semiconductor film and application. The preparation method comprises the following steps: selecting zinc acetate dihydrate as a precursor, ethylene glycol monomethyl ether as a solvent, ethanolamine as a stabilizer and ferric acetylacetonate as a doped metal compound; and heating and stirring until the solution is completely dissolved, standing for one day, spin-coating the mixed solution on a silicon wafer by adopting a sol-gel method, and annealing to obtain the required film. The method has the advantages of low cost, simple process, safety, environmental protection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor thin films, and in particular to a method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable luminescence wavelength, the iron-doped zinc oxide semiconductor thin film and applications thereof. Background Art

[0002] Zinc oxide thin film is an important wide-bandgap semiconductor material with a wide range of applications in optoelectronics, particularly in light-emitting diodes, lasers, and solar cells. By introducing iron as a dopant, the luminescence properties of this material, including its wavelength, can be effectively tuned.

[0003] Since zinc oxide has a wide band gap (3.37 eV) and a large exciton binding energy (60 meV), by doping with iron, the band structure of zinc oxide can be effectively adjusted and its electrical and optical properties can be changed. First of all, in order to obtain a film with stable performance, the distribution of iron in the film must be uniform. This requires high control during the film growth process, and the doping concentration directly affects the physical properties of the film. Therefore, accurate control of the doping concentration is crucial. Iron doping will affect the grain size and orientation of the zinc oxide film. Excessive grain size will reduce the transmittance of the film, and incorrect crystal orientation will lead to a decrease in the optical and electrical properties of the film. Iron doping will introduce new defects, such as oxygen vacancies, which will affect the performance of the film. Therefore, it is necessary to control the defect density to ensure the stability and reliability of the film. Summary of the Invention

[0004] Purpose of the invention: The present invention proposes a method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable luminescence wavelength and an application thereof, so as to solve the problems of difficult control of doping concentration and high production cost during the preparation of iron-doped zinc oxide thin films.

[0005] Technical solution: The present invention proposes a method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable luminescence wavelength, comprising the following steps:

[0006] (1) Weigh zinc acetate and ferric acetylacetonate separately, fully dissolve them in ethylene glycol monomethyl ether, then slowly add ethanolamine solution to the mixed solution, heat and stir the mixed solution of the four reactants until they are completely dissolved, and then let it stand for one day;

[0007] (2) The slurry sol prepared in step (1) is subjected to film formation by a slurry spinner to obtain a sample;

[0008] (3) The sample obtained in step (2) is placed in a tubular sintering furnace and heat-treated in an air atmosphere to obtain an iron-doped zinc oxide thin film sample after the reaction is completed.

[0009] Preferably, in step (1), the amount of zinc acetate is 0.01 mol, the doping atomic fractions of the iron acetylacetonate are 1.0%, 3.0%, 5.0%, and 7.0%, respectively, the amount of ethylene glycol methyl ether is 20 mL, and the amount of the ethanolamine solution is 0.01 mol.

[0010] Preferably, in step (1), the heating and stirring temperature is 60° C., the stirring time is 2 to 4 hours, and the standing time is 24 hours.

[0011] Preferably, the specific steps of step (2) are: the slurry sol prepared in step (1) is used to form a film using a slurry spreader, the above sol is dropped on the substrate adsorbed on the tray, the pre-rotation speed is controlled to 500r / min, and the time is controlled to 15s; the high-speed rotation speed is 3000r / min, the time is controlled to be 25s, the drying temperature is 400℃, the time is controlled to be 3min, 10 layers are spin-coated, and finally the sample is obtained.

[0012] Preferably, in step (3), the sintering temperature in air atmosphere is 800° C., and the heat preservation sintering time is 2 h.

[0013] Preferably, the heating rate of the heat treatment in step (3) is 5°C / min.

[0014] Beneficial effects: The present invention utilizes a simple and effective method to prepare a high-efficiency iron-doped zinc oxide thin film, which is beneficial for achieving stable control of the doping concentration and at the same time is beneficial for reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is an X-ray diffraction pattern of an iron-doped zinc oxide thin film sample according to an embodiment of the present invention;

[0016] Figure 2 This is a scanning electron microscope image of an iron-doped zinc oxide thin film sample according to an embodiment of the present invention;

[0017] Figure 3 This is a photoluminescence spectrum of an iron-doped zinc oxide thin film sample according to an embodiment of the present invention. DETAILED DESCRIPTION

[0018] The present invention will be further described below with reference to the examples, but the present invention is not limited to the following examples.

[0019] A method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable luminescence wavelength mainly comprises the following steps:

[0020] (1) Weigh 0.01 mol of zinc acetate and ferric acetylacetonate with doping atomic fractions of 1.0%, 3.0%, 5.0%, and 7.0%, respectively, and fully dissolve them in 20 mL of ethylene glycol methyl ether. Then, 0.01 mol of ethanolamine solution is slowly added to the above mixed solution. The mixed solution of the four reactants is magnetically stirred at 60°C for 2-4 hours and then left to stand for 24 hours.

[0021] (2) The prepared slurry sol was used to form a film using a slurry spinner. The sol was dropped onto the substrate adsorbed on the tray. The pre-rotation speed was controlled at 500 r / min and the time was controlled at 15 s. The high-speed rotation speed was controlled at 3000 r / min and the time was controlled at 25 s. The drying temperature was 400 ° C and the time was controlled at 3 min. Ten layers were spin-coated to finally obtain the sample.

[0022] (3) The sample was placed in a tubular sintering furnace and heat treated in an air atmosphere at a heating rate of 5°C / min, a heat treatment temperature of 800°C, and a holding time of 2 h. After the reaction was completed, an iron-doped zinc oxide thin film sample was obtained.

[0023] Iron-doped zinc oxide thin films can be used to modify their luminescence properties by adjusting the iron doping concentration and annealing conditions, enabling the fabrication of different light-emitting diodes. Furthermore, these films can be used to fabricate photodetectors for detecting light signals of specific wavelengths. Through various methods, such as dopant energy level regulation, concentration control, and structural optimization, the emission wavelength of iron-doped zinc oxide thin films can be effectively tuned to meet the application requirements of various optoelectronic devices.

[0024] Example 1

[0025] The first step is to weigh 0.01 mol of zinc acetate and 1.0% ferric acetylacetonate, respectively, and fully dissolve them in 20 mL of ethylene glycol methyl ether. Then, 0.01 mol of ethanolamine solution is slowly added to the above mixed solution, and the mixed solution of the four reactants is magnetically stirred at 60°C for 2 to 4 hours and left to stand for 24 hours.

[0026] In the second step, the prepared slurry sol is used to form a film using a slurry spreader. The above sol is dropped on the substrate adsorbed on the tray, the pre-rotation speed is controlled to 500r / min, and the time is controlled to 15s; the high-speed rotation speed is 3000r / min, the time is controlled to 25s, the drying temperature is 400℃, the time is controlled to 3min, 10 layers are spin-coated, and finally the sample is obtained.

[0027] In the third step, the sample is placed in a tubular sintering furnace and heat-treated in an air atmosphere at a heating rate of 5°C / min, a heat treatment temperature of 800°C, and a holding time of 2 hours. After the reaction is completed, an iron-doped zinc oxide thin film sample is obtained.

[0028] Figure 1 (a) is the XRD pattern of the Fe-doped ZnO thin film sample.

[0029] Figure 2 (a) is the SEM image of the iron-doped zinc oxide thin film sample.

[0030] Figure 3 (a) PL spectrum of the iron-doped zinc oxide thin film sample.

[0031] Example 2

[0032] The first step is to weigh 0.01 mol of zinc acetate and 3.0% of ferric acetylacetonate, respectively, and fully dissolve them in 20 mL of ethylene glycol methyl ether. Then, 0.01 mol of ethanolamine solution is slowly added to the above mixed solution, and the mixed solution of the four reactants is magnetically stirred at 60°C for 2 to 4 hours and left to stand for 24 hours.

[0033] In the second step, the prepared slurry sol is used to form a film using a slurry spreader. The above sol is dropped on the substrate adsorbed on the tray, the pre-rotation speed is controlled to 500r / min, and the time is controlled to 15s; the high-speed rotation speed is 3000r / min, the time is controlled to 25s, the drying temperature is 400℃, the time is controlled to 3min, 10 layers are spin-coated, and finally the sample is obtained.

[0034] In the third step, the sample is placed in a tubular sintering furnace and heat treated in an air atmosphere with a heating rate of 5°C / min, a heat treatment temperature of 800°C, and a holding time of 2h. After the reaction is completed, an iron-doped zinc oxide thin film sample is obtained.

[0035] Figure 1 (b) is the XRD pattern of the iron-doped zinc oxide thin film sample.

[0036] Figure 2 (b) is the SEM image of the iron-doped zinc oxide thin film sample.

[0037] Figure 3 (b) PL spectrum of the iron-doped zinc oxide thin film sample.

[0038] Example 3

[0039] The first step is to weigh 0.01 mol of zinc acetate and 5.0% doping atomic fraction of iron acetylacetonate respectively, and fully dissolve them in 20 mL of ethylene glycol methyl ether. Then, 0.01 mol of ethanolamine solution is slowly added to the above mixed solution, and the mixed solution of the four reactants is magnetically stirred at 60°C for 2 to 4 hours and left to stand for 24 hours.

[0040] In the second step, the prepared slurry sol is used to form a film using a slurry spreader, and the above sol is dropped on the substrate adsorbed on the tray, and the pre-rotation speed is controlled to 500r / min; the time is controlled to 15s; the high-speed rotation speed is 3000r / min, the time is controlled to 25s, the drying temperature is 400℃, the time is controlled to 3min, 10 layers are spin-coated, and finally the sample is obtained.

[0041] In the third step, the sample is placed in a tubular sintering furnace and heat-treated in an air atmosphere at a heating rate of 5°C / min, a heat treatment temperature of 800°C, and a holding time of 2 hours. After the reaction is completed, an iron-doped zinc oxide thin film sample is obtained.

[0042] Figure 1 (c) is the XRD pattern of the Fe-doped ZnO thin film sample.

[0043] Figure 2 (c) is the SEM image of the iron-doped zinc oxide thin film sample.

[0044] Figure 3 (c) PL spectrum of the iron-doped zinc oxide thin film sample.

[0045] Example 4

[0046] The first step is to weigh 0.01 mol of zinc acetate and 7.0% doping atomic fraction of iron acetylacetonate respectively, and fully dissolve them in 20 mL of ethylene glycol methyl ether. Then, 0.01 mol of ethanolamine solution is slowly added to the above mixed solution, and the mixed solution of the four reactants is magnetically stirred at 60°C for 2 to 4 hours and left to stand for 24 hours.

[0047] In the second step, the prepared slurry sol is used to form a film using a slurry spreader. The above sol is dropped on the substrate adsorbed on the tray, the pre-rotation speed is controlled to 500r / min, and the time is controlled to 15s; the high-speed rotation speed is 3000r / min, the time is controlled to 25s, the drying temperature is 400℃, the time is controlled to 3min, 10 layers are spin-coated, and finally the sample is obtained.

[0048] In the third step, the sample is placed in a tubular sintering furnace and heat-treated in an air atmosphere at a heating rate of 5°C / min, a heat treatment temperature of 800°C, and a holding time of 2 hours. After the reaction is completed, an iron-doped zinc oxide thin film sample is obtained.

[0049] Figure 1 (d) is the XRD pattern of the Fe-doped ZnO thin film sample.

[0050] Figure 2 (d) is the SEM image of the iron-doped zinc oxide thin film sample.

[0051] Figure 3(d) PL spectrum of the iron-doped zinc oxide thin film sample.

[0052] Detailed description with accompanying drawings

[0053] Figure 1 Figure 2 shows the XRD patterns of Fe-doped ZnO films. As can be seen from the figure, all four Fe-doped ZnO films exhibit a strong (002) diffraction peak near 34.49°, indicating that the films have a ZnO wurtzite structure and grow preferentially along the c-axis. In addition to the (002) diffraction peak, the XRD patterns also show diffraction peaks at (100), (101), and (102), indicating that the grown samples are polycrystalline films.

[0054] Figure 2 The SEM image of the iron-doped zinc oxide sample is shown in Figure 2. Figure 2 As can be seen, the surface of the Fe-doped ZnO film is very flat and dense. The average grain sizes of the Fe-doped ZnO films are approximately 55 nm, 50 nm, 50 nm, and 40 nm, respectively. The effect of different Fe doping concentrations on the average grain size of the ZnO films is not significant, but the average grain size decreases with increasing Fe doping concentration.

[0055] Figure 3 The following are PL spectra of iron-doped zinc oxide thin films. For the 1.0% atomic percent Fe-doped ZnO thin film, strong green emission is observed around 540 nm. This green emission originates from both transitions of monoionized oxygen vacancies to the valence band top and Fe substitutional Zn donor defects to the valence band top. For the 3.0% atomic percent Fe-doped ZnO thin film, green emission appears around 540 nm, and a blue peak appears around 480 nm. Surface ions capture a large number of holes near the valence band, generating blue emission through electron-hole recombination. The emission peak at 506 nm originates from transitions of monoionized oxygen vacancies, while the emission at 572 nm is attributed to transitions of Fe substitutional Zn donor defects to the valence band top. When the Fe doping level is further increased to 5.0 and 7.0 at%, the emission center shifts to around 610 nm, and the emission intensity decreases significantly.

Claims

1. A method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable luminescence wavelength, characterized in that: The following steps are involved: (1) Weigh zinc acetate and ferric acetylacetonate respectively, fully dissolve them in ethylene glycol methyl ether, then slowly add ethanolamine solution into the mixed solution, heat and stir the mixed solution of the four reactants until they are completely dissolved, and then let it stand for one day; (2) using a slurry sol prepared in step (1) to form a film using a slurry spinning machine to obtain a sample; (3) placing the sample obtained in step (2) in a tubular sintering furnace and subjecting it to heat treatment in an air atmosphere, and obtaining an iron-doped zinc oxide thin film sample after the reaction is completed.

2. The method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable emission wavelength according to claim 1, characterized in that: In the step (1), the zinc acetate is 0.01 mol, the doping atomic fractions of the iron acetylacetonate are 1.0%, 3.0%, 5.0% and 7.0% respectively, the ethylene glycol methyl ether is 20 mL, and the ethanolamine solution is 0.01 mol.

3. The method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable emission wavelength according to claim 1, characterized in that: In the step (1), the heating and stirring temperature is 60° C., the stirring time is 2 to 4 hours, and the standing time is 24 hours.

4. The method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable emission wavelength according to claim 1, characterized in that: The specific steps of step (2) are: using a slurry sol prepared in step (1) to form a film using a slurry homogenizer, dripping the above sol on a substrate adsorbed on a tray, controlling the pre-rotation speed to 500 r / min, and the time to 15 s; the high-speed rotation speed is 3000 r / min, the time is controlled to be 25 s, the drying temperature is 400°C, the time is controlled to be 3 min, and 10 layers are spin-coated to finally obtain a sample.

5. The method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable emission wavelength according to claim 1, characterized in that: In the step (3), the sintering temperature in the air atmosphere is 800° C., and the sintering time is 2 hours.

6. The method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable emission wavelength according to claim 1, characterized in that: The heating rate of the heat treatment in step (3) is 5°C / min.

7. An iron-doped zinc oxide semiconductor thin film obtained by the method for preparing an iron-doped zinc oxide semiconductor thin film with adjustable emission wavelength according to any one of claims 1 to 6.

8. Use of the iron-doped zinc oxide semiconductor film as claimed in claim 7 in a light emitting diode.

9. Use of the iron-doped zinc oxide semiconductor film as claimed in claim 7 in a laser.

10. Use of the iron-doped zinc oxide semiconductor film as claimed in claim 7 in a solar cell.